Intracellular VHHs to monitor and modulate GPCR signaling - Raynaud, Pauline; Gauthier, Camille; Jugnarain, Vinesh; Jean-Alphonse, Frédéric; Reiter, Eric; Bruneau, Gilles; Crépieux, Pascale (Frontiers in Endocrinology, 2022)
Single-domain antibody fragments, also known as VHH or nanobodies, have opened promising avenues in therapeutics and in exploration of intracellular processes. Because of their unique structural properties, they can reach cryptic regions in their cognate antigen. Intracellular VHH/antibodies primarily directed against cytosolic proteins or transcription factors have been described. In contrast, few of them target membrane proteins and even less recognize G protein-coupled receptors. This class of receptors are major therapeutic targets, which reflects their involvement in a plethora of physiological responses. Hence, they elicit a tremendous interest in the scientific community and in the industry. Comprehension of their pharmacology has been obscured by their conformational complexity, that has precluded deciphering their structural properties until the early 2010’s. To that respect, intracellular VHH have been instrumental in stabilizing G protein-coupled receptors in active conformations in order to solve their structure, possibly bound to their primary transducers, G proteins or β-arrestins. In contrast, the modulatory properties of VHH recognizing the intracellular regions of G protein-coupled receptor on the induced signaling network have been poorly studied. In this review, we will present the advances that the intracellular VHH have permitted in the field of GPCR signaling and trafficking. We will also discuss the methodological hurdles that linger the discovery of modulatory intracellular VHH directed against GPCR, as well as the opportunities they open in drug discovery.